2020
DOI: 10.1038/s41467-020-19614-y
|View full text |Cite
|
Sign up to set email alerts
|

Genomic signatures of recombination in a natural population of the bdelloid rotifer Adineta vaga

Abstract: Sexual reproduction is almost ubiquitous among extant eukaryotes. As most asexual lineages are short-lived, abandoning sex is commonly regarded as an evolutionary dead end. Still, putative anciently asexual lineages challenge this view. One of the most striking examples are bdelloid rotifers, microscopic freshwater invertebrates believed to have completely abandoned sexual reproduction tens of Myr ago. Here, we compare whole genomes of 11 wild-caught individuals of the bdelloid rotifer Adineta vaga and present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 82 publications
(126 reference statements)
3
47
0
Order By: Relevance
“…Initial evidence of long-term asexuality ( Flot et al, 2013 ; Mark Welch and Meselson, 2000 ) has been refuted by later studies or confounded by alternative explanations ( Mark Welch et al, 2008 ; Nowell et al, 2018 ; Simion et al, 2020 ). Some recent studies have proposed alternative modes of inter-individual genetic exchange, but these suggestions would require exotic mechanisms unknown in other animals ( Flot et al, 2013 ; Signorovitch et al, 2015 ), or rates of sex that are difficult to reconcile with the lack of observed males ( Vakhrusheva et al, 2020 ). While the precise genetic system in bdelloids remains an open question, nonetheless they provide a unique test-case for models of TE evolution when conventional sex is absent or strikingly rare.…”
Section: Introductionmentioning
confidence: 99%
“…Initial evidence of long-term asexuality ( Flot et al, 2013 ; Mark Welch and Meselson, 2000 ) has been refuted by later studies or confounded by alternative explanations ( Mark Welch et al, 2008 ; Nowell et al, 2018 ; Simion et al, 2020 ). Some recent studies have proposed alternative modes of inter-individual genetic exchange, but these suggestions would require exotic mechanisms unknown in other animals ( Flot et al, 2013 ; Signorovitch et al, 2015 ), or rates of sex that are difficult to reconcile with the lack of observed males ( Vakhrusheva et al, 2020 ). While the precise genetic system in bdelloids remains an open question, nonetheless they provide a unique test-case for models of TE evolution when conventional sex is absent or strikingly rare.…”
Section: Introductionmentioning
confidence: 99%
“…No inconsistencies in evolutionary trajectories are known between mitochondrial and nuclear markers in Adineta vaga , the only morphological species for which the hypothesis of multi‐locus phylogenetic congruence was explicitly tested (Debortoli et al, 2016; Wilson et al, 2018), and which is also one of the species we included in our analyses. The confounding effects of Horizontal Gene Transfer, a mechanisms that led to an estimate of about 10% of foreign genes currently occurring in bdelloid genomes (Nowell et al, 2018), and of the potential for recombination in bdelloids (Vakhrusheva et al, 2020) are still too rare to leave signatures in a comparative study of within‐species diversification (Eyres et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The main aim of this study is to provide further understanding on the evolutionary history of a group of Antarctic terrestrial animals, the bdelloid rotifers. Bdelloid rotifers are microscopic animals characterised by freezing and desiccation resistance (Kaczmarek et al, 2019), by unclear asexuality (Vakhrusheva et al, 2020), and by unique genomic features (Nowell et al, 2018). They are ubiquitous in the ice‐free areas of Antarctica (Garlasché et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It might, however, yet be relevant when considering how obligate asexuals tolerate deleterious mutation, not least because even low levels of CO can have a large genome purging effect [ 79 ]. Recent analysis [ 81 ] of bdelloid rotifers, a species with no observed males and thought to be anciently asexual [ 80 ], indeed shows classical patterns of linkage disequilibrium (LD) decay over genomic distance, consistent with the activity of somatic recombination in an asexual lineage [ 81 ]. Similarly, prior analysis indicates that their chromosomal arrangement is incompatible with classical meiosis but, nonetheless, the genome reveals extensive (presumably mitotic) GC [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, prior analysis indicates that their chromosomal arrangement is incompatible with classical meiosis but, nonetheless, the genome reveals extensive (presumably mitotic) GC [ 82 ]. While it is possible that bdelloids may not be truly obligately asexual [ 81 ], it is likely, in a rarely sexual organism, that somatic recombination and GC will play a more significant role, as regards protection from deleterious mutations [ 82 ], than in regularly sexual species. It also follows that inference of meiotic recombination rates from LD decay data would overestimate the impact of meiotic CO.…”
Section: Discussionmentioning
confidence: 99%